2017
DOI: 10.1038/s41598-017-11654-7
|View full text |Cite
|
Sign up to set email alerts
|

ApoE4-associated phospholipid dysregulation contributes to development of Tau hyper-phosphorylation after traumatic brain injury

Abstract: The apolipoprotein E4 (ApoE4) genotype combines with traumatic brain injury (TBI) to increase the risk of developing Alzheimer’s Disease (AD). However, the underlying mechanism(s) is not well-understood. We found that after exposure to repetitive blast-induced TBI, phosphoinositol biphosphate (PIP2) levels in hippocampal regions of young ApoE3 mice were elevated and associated with reduction in expression of a PIP2 degrading enzyme, synaptojanin 1 (synj1). In contrast, hippocampal PIP2 levels in ApoE4 mice did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 71 publications
(87 reference statements)
2
30
0
Order By: Relevance
“…Interestingly, a link was also recently made between ApoE4, TBI, and tau phosphorylation. Cao and colleagues found that ApoE4 knock-in mice had significantly more phosphorylated tau following blast TBI than ApoE3 knock-in mice, via activation of GSK3β [ 271 ]. In addition, recent transcriptional profiling of ApoE4 and ApoE3 knock-in mice at 14 days post-TBI found significant upregulation in TREM2, TYROBP, C-type lectin domain containing 7A, Cd68, and CX3CR1 compared to the sham control [ 272 ].…”
Section: Acute Damage To the Brain Triggers Inflammation And Increasementioning
confidence: 99%
“…Interestingly, a link was also recently made between ApoE4, TBI, and tau phosphorylation. Cao and colleagues found that ApoE4 knock-in mice had significantly more phosphorylated tau following blast TBI than ApoE3 knock-in mice, via activation of GSK3β [ 271 ]. In addition, recent transcriptional profiling of ApoE4 and ApoE3 knock-in mice at 14 days post-TBI found significant upregulation in TREM2, TYROBP, C-type lectin domain containing 7A, Cd68, and CX3CR1 compared to the sham control [ 272 ].…”
Section: Acute Damage To the Brain Triggers Inflammation And Increasementioning
confidence: 99%
“…ApoE4 is also linked to a greater incidence of moderate or severe contusions [35] as well as concussions [36]. ApoE4 genotype combined with TBI is thought to increase the risk of developing Tauopathy and Alzheimer's Disease [37] as well as post-traumatic epilepsy [38] and impaired spontaneous blood brain barrier repair [24]. Neurogenesis is affected in an ApoE isoform-dependent manner after both ischemic stroke [39] and controlled cortical impact [17] in mouse models but not after concussion [40].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have addressed tau processing in experimental animal models of blast TBI, with many reporting elevated levels of tau in brain or blood [21,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65]. Two studies reported the presence of tau oligomers following blast exposure [59,61] and others have suggested that p-tau metabolism following blast may be regulated by APOE genotype [62]. P-tau-like accumulations have also been observed in mouse retinal neurons and glia following blast injury [66], and in the superficial layers of the cerebral cortex [21].…”
Section: Discussionmentioning
confidence: 99%